The suap gula ceremony & the sugar connection / Nazima Versay Kudus - Versay Kudus, Nazima (Academy of Language Studies, 2023)
Sugar is an ever present condiment in most kitchens. Common types of sugar found in Malaysia are granulated sugar, caster sugar, icing sugar, brown sugar, gula melaka (sugar made from the saps of coconut palm) and gula apong (sugar processed from nipa palm). Sugar or 'gula' in Malay, has important references in the Malay culture. For instance, in the Jawi Peranakan culture (refers to locally born, Malay-speaking Muslims of South Asian or Arab and Malay ancestry during the British Colonial Administration in Malaya), the engagement ceremony (meminang) is called the suap gula. Some of their descendents today still practise this tradition which literally means 'feeding some sugar' to the lady. This is usually done by the elder women in the man's family: his mother or grandmother will suap gula the fiancée-to-be and then slip the engagement ring onto her finger. Sugar is used to symbolise a 'sweet' and happy relationship. These actions marked an engagement between the man and women, and they are now a fiancé and a fiancée.